The influence of Self-Regulated Learning on Academic Anxiety in Final Year Students of the Psychology Faculty, Makassar State University - Melinda Melinda; Ahkam Alwi; Andi Halima (Polteknik Ilmu Pemasyarakatan, 2023)
This study aims to determine the effect of self-regulated learning on academic anxiety in class 2019 students at the Faculty of Psychology, Makassar State University. research methods using quantitative methods. The population in this study were all 2019 batch students of the psychology faculty at Makassar State University with the sampling technique using the simple random sampling method. The results of the study involving 163 students of the 2019 batch of psychology at Makassar State University showed that there was an effect of self- regulated learning on academic anxiety in psychology students of 2019 Makassar State University with a significance value of 0.009 with a self-regulated learning contribution of 4.1%. The implications of this study are expected to be a consideration for future researchers to pay more attention to other factors that can influence academic anxiety.